Visceral fat measured by DXA is associated with increased risk of non-spine fractures in nonobese elderly women: a population-based prospective cohort analysis from the São Paulo Ageing & Health (SPAH) Study. Issue 12 (December 2016) - Machado, L.; Domiciano, D.; Figueiredo, C.; Caparbo, V.; Takayama, L.; Oliveira, R.; Lopes, J.; Menezes, P.; Pereira, R.
Abstract Summary The present study investigates the relationship between visceral fat measured by dual-energy X-ray absorptiometry (DXA) and the incidence of non-spine fractures in community-dwelling elderly women. We demonstrated a potential negative effect of visceral fat on bone health in nonobese women. Introduction The protective effect of obesity on bone health has been questioned because visceral fat has been demonstrated to have a deleterious effect on bone. The aim of this study was to investigate the association of visceral fat measured by DXA with the incidence of non-spine fractures in community-dwelling elderly women. Methods This longitudinal prospective population-based cohort study evaluated 433 community-dwelling women aged 65 years or older. A specific clinical questionnaire, including personal history of a fragility fracture in non-spine osteoporotic sites, was administered at baseline and after an average of 4.3 years. All incidences of fragility fractures during the study period were confirmed by affected-site radiography. Visceral adipose tissue (VAT) was measured in the android region of a whole-body DXA scan. Results The mean age was 72.8 ± 4.7 years, and 28 incident non-spine osteoporotic fractures were identified after a mean follow-up time of 4.3 ± 0.8 years. According to the Lipschitz classification for nutritional status in the elderly, 38.6 % of women were nonobese (BMI ≤ 27 kg/m2 ) and 61.4 % were obese/overweight. Logistic regression models were used to estimate the relationship between VAT and non-spine fractures in elderly women. After adjusting for age, race, previous fractures, and BMD, VAT (mass, area, volume) had a significant association with the incidence of non-spine fractures only in nonobese elderly women (VAT mass: OR, 1.42 [95 % CI, 1.09–1.85;p = 0.010]; VAT area: OR, 1.19 [95 % CI, 1.05–1.36;p = 0.008]; VAT volume: OR, 1.40 [95 % CI, 1.09–1.80;p = 0.009]). Conclusion This study suggests a potential negative effect of visceral adiposity on bone health in nonobese women.